Integration of Vegetables and Fish with Rice in Rain-Fed Farmland: Towards Sustainable Agriculture - Md. Abu Sayed Jewel; Md. Ayenuddin Haque; S. M. Wahed Ali; Mst. Eliza Pervin; Md. Giush Uddin Ahmed; M. Shahanul Islam; Mohammad Belal Hossain; Mohammed Fahad Albeshr; Takaomi Arai (Agriculture, 2023)
Sustainability in aquaculture or agriculture production is depended on its successive use of natural resources that can ensure economic increment and sustainability of the livelihood of people. The objective of the study was to find out suitable combination of rice-fish-vegetable to be cultured in rainfed rice field. Two experiments were conducted for 4 months under rainfed condition. Two rice varieties (BRRI-51 and BRRI-52), three different fish species. i.e., Cyprinus carpio var. communis, Barbonymus gonionotus and Oreochromis niloticus and two combinations of vegetables (Red amaranth + Indian spinach and Cucumber + Water spinach) were selected for these experiments. Significantly higher growth and production performance of fish, B. gonionotus were recorded in both of the experiments. Furthermore, between the rice varieties, BRRI-52 showed significantly higher grain yield, biological yield and harvest index. However, vegetable combination did not show any significant difference between the experiment. Finally, considering economic performance, integration of BRRI-52, B. gonionotus and Cucumber-spinach combinations was provided significantly higher net benefit and benefit-cost ratio (BCR). Therefore, combination of rice-fish-vegetable BRRI-52, B. gonionotus and Cucumber-spinach is recommended to improve food security and sustainability for resource-limited farmers in rainfed rice field. Rice-fish-vegetable integrated culture could address the sustainable development goals (SDG) and therefore policy implications should be considered for institutional support, technical facilities and extension services to increase the knowledge of farmers and to uplift the productivity and profitability.